Influence of abiotic factors on indole-3-acetic acid production by indigenous diazotrophic isolates of Bacillus sp. - Veerasamy, Piriya Latha; Wong, Sing King; Abdul Aziz, Zakry Fitri; Kasim, Susilawati (2012)
Exogenous indole-3acetic acid (IAA) plays an important role in formation and initiation of main, lateral and adventitious roots in vegetative propagation. The hormone is produced by certain soil-plant associated rhizobacteria. However, IAA synthesis by rhizobacteria is influenced by abiotic growth condition. Three indigenous Bacillus isolates were subject to in vitro assay for the effects of abiotic factors (light temperature, salinity and pH) on IAA production. Bacillus cereus UPMLH 1 and UPMLH 24 were able to produce higher level of IAA in dark than under 12 hours light. Bacillus megaterium UPMLH3 produced optimal level of IAA in both 12 hours light period and dark condition. All isolates grew well between 25-40C, however only B. megaterium was capable to synthesis IAA (21.15pg/ml) at 40C. B. cereus UPMLH1 and UPMLH24 revealed higher IAA production in slightly alkaline condition (pH8). B. cereus UPMLH24 has high tolerance to salinity up to 5% NaCI. B. cereus UPMLH1. B. megaterium UPMLH3 and B. cereus UPMLH24 might serve as potential biofertilizer which could enhance growth performance of test plants.